DESIGN APROACH AND CONSTRUCTION OF A NEW PORT OF NAUTICAL TOURISM IN PORTONOVI - Paolo Galvanin; Andreina Piacentini; Duško Lučić; Ivana Tešović; Radomir Zejak; Goran Sekulić; Radenko Pejović; Goran Gorašević; Miloš Knežević; Zlatko Zafirovski; Mladen Muhadinović; Miodrag Bujišić (Association of structural engineers of Serbia, 2016)
The municipality of Herceg Novi projected a wide development known as Portonovi in Kumbor, which is a world class resort with a Port for nautical tourism. The port is formed through the construction of two main fixed jetties which extend 200 m in length from the existing coast line and encapsulate the marina basin. The new jetties are designed as pre-cast decks supported by concrete bored pile; the design takes into account problems related to geotechnical conditions, seismicity, durability in the sea water.
Keywords: Marina works, port of nautical tourism, liquefaction